Validation of Online Fear of Missing Out (ON-FoMO) Scale in Indonesian Version - Rizal Kurniawan; Rahayu Hardianti Utami (Jurnal Neo Konseling, 2022)
The main objective of this study was to examine the psychometric properties of the online fear of missing out (ON-FoMO) scale in the Indonesian version. This research consists of two stages. In the first stage, this study also examines the dimensional structure of the ON-FoMO scale. A total of 327 respondents were involved in this process. The analysis used is exploratory factor analysis (EFA). In the second stage, this study was conducted to test the validity of the ON-FoMO scale. This test was carried out by calculating the correlation of the ON-FoMO scale with the fear of missing out (FoMO) scale and the big five inventory personality. This process involved as many as 245 respondents. This study indicates that the scale dimensions formed from the EFA testing process are the same as the dimensions of the original scale, namely four dimensions: anxiety, need to belong, addiction, and need for popularity. The anxiety dimension has contributed to the most significant variance value, 17.85%. The correlation of the four dimensions of ON-FoMO ranged from  r = .41 to r = .21. The results of the convergent validity test showed that the ON-FoMO scale was significantly correlated with the FoMO scale, neuroticism personality type, and openness personality type. Overall, the ON-FoMO scale has good validity. The correlation between ON-FoMO and the openess personality types is further discussed.